A Comparison of Hand-Sewn Versus Stapled Ileal Pouch Anal Anastomosis (IPAA) Following Proctocolectomy: A Meta-Analysis of 4183 Patients - Lovegrove, Richard E.; Constantinides, Vasilis A.; Heriot, Alexander G.; Athanasiou, Thanos; Darzi, Ara; Remzi, Feza H.; Nicholls, R John; Fazio, Victor W.; Tekkis, Paris P. (Annals of surgery, 2006)
Using meta-analytical techniques, the study compared postoperative adverse events and functional outcomes of stapled versus hand-sewn ileal pouch-anal anastomosis (IPAA) following restorative proctocolectomy. The choice of mucosectomy and hand-sewn versus stapled pouch-anal anastomosis has been a subject of debate with no clear consensus as to which method provides better functional results and long-term outcomes. Comparative studies published between 1988 and 2003, of hand-sewn versus stapled IPAA were included. Endpoints were classified into postoperative complications and functional and physiologic outcomes measured at least 3 months following closure of ileostomy or surgery if no proximal diversion was used, quality of life following surgery, and neoplastic transformation within the anal transition zone. Twenty-one studies, consisting of 4183 patients (2699 hand-sewn and 1484 stapled IPAA) were included. There was no significant difference in the incidence of postoperative complications between the 2 groups. The incidence of nocturnal seepage and pad usage favored the stapled IPAA (odds ratio [OR] = 2.78, P < 0.001 and OR = 4.12, P = 0.007, respectively). The frequency of defecation was not significantly different between the 2 groups (P = 0.562), nor was the use of antidiarrheal medication (OR = 1.27, P = 0.422). Anorectal physiologic measurements demonstrated a significant reduction in the resting and squeeze pressure in the hand-sewn IPAA group by 13.4 and 14.4 mm Hg, respectively (P < 0.018). The stapled IPAA group showed a higher incidence of dysplasia in the anal transition zone that did not reach statistical significance (OR = 0.42, P = 0.080). Both techniques had similar early postoperative outcomes; however, stapled IPAA offered improved nocturnal continence, which was reflected in higher anorectal physiologic measurements. A risk of increased incidence of dysplasia in the ATZ may exist in the stapled group that cannot be quantified by this study. We describe a decision algorithm for the choice of IPAA, based on the relative risk of long-term neoplastic transformation.